Local Component in the Literary Idiolect of the Writers from Brest Region (Linguostylistic Studies, 2019)
Modern studies of the writers’ individual style features lay emphasis on the importance of elucidating the creative approach to the issues of native speakers’ language means and introducing dialectisms in the artistic texts. Taking into account that artistic languge is intrinsic for the activity of artists of the world, the author's usage of communication means is always associated with his perception of the world, and his sense of language. In literary idiolect, the author's linguistic specification provides for the usage of dialectism as a component of the author's language system. The article analyzes the dialects in the artistic context of the Brest region writers (V. Hnilomedova, G. Marchuk, N. Kupreiev).The emphasis iis laid on the functions of the local language units (set expressions, dialectisms, obsolete words) in the idiolect of the Brest region writers. The author analyzes the structural and semantic features of dialectisms. The issues of function and semantics of dialectisms, obsolete words and set expressions in the idiolect of the writers of Brest region are topical since few attempts have been made to investigate them. With the help of outdated words and ethnographic dialectisms, the writers convey historical events, the life of Bresteians, the ethnographic originality of the Western Belarus village in the 20s of the twentieth century. The The study has revealed peculiar features of the usage of dialectisms at different levels (phonetic, grammatical, word-forming, lexical and semantic). The peculiarity of the the characters’ speech in the literary works is conveyed via the usage of phonetic, grammatical and word-forming dialectisms. Brest region writers introduce dialect words into the literary context usually by «quoting», therefore the presence of dialectisms in the text is an element of another style. The article highlights two main functions of a dialect word in an artistic context: firstly, for realistic reflection of village life and creation of ethnographic colouring; and secondly, as the language characteristics of the literary work characters and for the individualization of speech.
Keywords: literary idiolect; dialecticism; set expression; obsolete word